The Influence of Ownership structure, Leverage, Size and Liquidity to the Policy of Dividend and Profitability as Intervening Variables in Service Sector Companies in BEI for period of 2012 – 2016 - Hais Dama (AIBPM Publisher, 2019)
This research was aimed to analyze (1) The direct influence of ownership structure, leverage, firm size and liquidity to profitability, (2) The direct influence of ownership structure, leverage, firm size and liquidity to dividend policy, (3) The indirect influence of ownership structure, leverage , firm size and liquidity against dividend policy through profitability. The Population in this research were all company in service area in Indonesia Stock Exchange period year 2012-2015 with sample of reasearch was 75 company. The sampling technique was done by purposive sampling with data analsisis technique that was by descriptive quantitative method, using SEM application analysis tool. The results obtained that, (1) The ownership structure, firm size and liquidity directly have a positive and significant impact on profitability, but leverage has no significant effect on profitability. (2) The ownership structure, leverage, firm size, and liquidity are directly influential and significant to the dividend policy, (3) The ownership structure, leverage, firm size, and liquidity directly and significantly to dividend policy through profitability.